Ligature-induced periodontitis induces systemic inflammation but does not alter acute outcome after stroke in mice. Issue 2 (February 2020) - O'Boyle, Conor; Haley, Michael J; Lemarchand, Eloise; Smith, Craig J; Allan, Stuart M; Konkel, Joanne E; Lawrence, Catherine B
Background: Stroke is a major cause of disability and mortality. Poorer outcome after stroke is associated with concomitant inflammatory and infectious disease. Periodontitis is a chronic inflammatory disease of the dental supporting structures and is a prominent risk factor for many systemic disorders, including cardiovascular disease and stroke. While epidemiological studies suggest that periodontitis increases the likelihood of stroke, its impact on stroke severity is poorly understood. Here, we sought to determine the contribution of periodontitis to acute stroke pathology. Methods: We characterized a murine ligature model of periodontitis for inflammatory responses that could potentially impact stroke outcome. We applied this model and then subjected mice to either transient or permanent middle cerebral artery occlusion. We also enhanced the periodontitis model with repeated intravenous administration of a periodontal-specific lipopolysaccharide to better mimic the clinical condition. Results: Ligature-induced periodontitis caused bone loss, bacterial growth, and increased local inflammatory cell trafficking. Systemically, periodontitis increased circulating levels of pro-inflammatory cytokines, and primed bone marrow monocytes to produce elevated tumour necrosis factor-alpha (TNFα). Despite these changes, periodontitis alone or in tandem with repeated lipopolysaccharide challenge did not alter infarct volume, blood–brain barrier breakdown, or systemic inflammation after experimental stroke. Conclusions: Our data show that despite elevated systemic inflammation in periodontitis, oral inflammatory disease does not impact acute stroke pathology in terms of severity, determined primarily by infarct volume. This indicates that, at least in this experimental paradigm, periodontitis alone does not alter acute outcome after cerebral ischemia.